Defining optimum quality of healthcare spaces through usability: case study on labour delivery room designs in Malaysian public hospitals - Mohd Nawawi, Norwina (2013)
Malaysian current healthcare facilities, as legacy of the colonial governments of the Portuguese, the Dutch and the British, were derived from the Western medicine and culture. Malaysia, through the transformation programme towards a developed nation in her own mould, i.e. of Asian, and in particularly, of Malaysian culture, seek to identify process of design of healthcare spaces derived from the Malaysian culture herself. The objective of this research was to determine the optimum space for healthcare performance through identifying “critical dimension” of a selected healthcare space to function safely and effectively through behavioural and cultural use of space as basis for other Malaysian public healthcare spaces, in determining healthcare facilities space standards. Both qualitative and quantitative approach, through case studies and phenomenology were adopted for this research via observations, interviews, site measurements and literature review. Results of the research through data collected and analyses of more than 7 public hospitals non-standard LDR designs for safe and effective critical dimension for safe and effective use, among others, were that, there were ranges of overall sizes and configurations which were generally based on “typical floor area based on foreign standards, practice and room data discussion outcome pre construction” standard. The less effective LDR design spaces, where critical dimension for safe and effective use were seen as being compromised, were overcome by the sheer carefulness of the staff in complementing the design through on site adjustment operational use and familiarity of the site i.e. adapting function to space. As a conclusion, although Malaysian culture are seen as a tolerable culture, accepting and adapting to circumstances whatever it may be to fit how ones work and go on with life, as there were no complains to how the design of healthcare spaces had been received from users once handed over. For Malaysians silence is a sign can be either of consent or no business next time round i.e. being ignored nor invited. As designers, to design any space or facilities related to culture, a phenomenological approach to how the space is use in comparison to the how it should be utilised for an effective and quality care should be the norm. Never take silence as a sign of quality work. For design that cares it pays to observe.